1838 Iowa Acts 449 - (:unkn) unknown (My University, 1838)
An Act to Prevent Disasters on Steam Boats, Navigating the Waters Within the Jurisdiction of the Territory of Iowa, §§ 11-12: Required the master and officers of a steam boat carrying gun powder to store the same in the safest part of the vessel, separate from articles likely to create combustion and would not require carry of any lighted lamp, torch, or candle. Also required persons bringing gun powder onto the boat to inform the master and officers. Violators fined not more than one hundred dollars.
Keywords: GUNPOWDER - TRANSPORTATION